A community sustainability ecosystem modeling for water supply business in thailand - Sukma, Narongsak; Leelasantitham, Adisorn (Frontiers in Environmental Science, 2022)
The Sustainable Development Goals were designed by the United Nations to help all organizations understand that any development must be balanced with the three pillars of sustainability: society, economy, and environment. Therefore, every organization must be more vigilant before introducing something that could have social consequences. This study aims to investigate all of the necessary components for proposing and establishing a community sustainability ecosystem model that supports local business sustainability with participation by highlighting essential variables that foster sustainable business prospects. The researcher distributed a questionnaire on a five-point Likert scale to 1,000 community water users in Thailand and received 627 valid responses. Using a simple random sampling technique with a sampling ratio of 14 villages, data was obtained. Subsequently, descriptive statistics are used to characterize the data (frequency distributions, percentages, averages, medians, and standard deviations). Furthermore, PLS-SEM was used to examine the relationships between factors and to launch the conceptual model using PLS path modeling. This study aimed to enhance the original Commitment-Trust theory relying on sustainability by examining the relationships between accepted variables pertaining to change agents, stakeholders, transparency, social networking, and good governance in order to provide new knowledge to the sustainability community and local sustainability businesses. In addition, this conceptual model can be applied to new business cases in which businesses need a framework that can be followed rapidly and reduces the danger of making mistakes on their own. In light of these considerations, this article proposes a novel community sustainability ecosystem model that may be adopted by the majority of businesses as a framework for managing the entire firm. Not only does it aid local businesses, but it can also adapt to any business change in order to become more profitable and sustainable.